2007
DOI: 10.1105/tpc.106.049981
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis E3 SUMO Ligase SIZ1 Regulates Plant Growth and Drought Responses

Abstract: Posttranslational modifications of proteins by small ubiquitin-like modifiers (SUMOs) regulate protein degradation and localization, protein-protein interaction, and transcriptional activity. SUMO E3 ligase functions are executed by SIZ1/SIZ2 and Mms21 in yeast, the PIAS family members RanBP2, and Pc2 in human. The Arabidopsis thaliana genome contains only one gene, SIZ1, that is orthologous to the yeast SIZ1/SIZ2. Here, we show that Arabidopsis SIZ1 is expressed in all plant tissues. Compared with the wild ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
313
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(329 citation statements)
references
References 57 publications
11
313
0
5
Order By: Relevance
“…SIZ1 has been shown to modulate gene expression in response to HR, BR, and ABA signaling, as well as during the transition to flowering (22,26,(45)(46)(47)(48). For example, SIZ1 regulates systemicacquired resistance through both NONEXPRESSOR OF PR1 (NPR1) gene-dependent and SA accumulation-dependent pathways (45).…”
Section: Discussionmentioning
confidence: 99%
“…SIZ1 has been shown to modulate gene expression in response to HR, BR, and ABA signaling, as well as during the transition to flowering (22,26,(45)(46)(47)(48). For example, SIZ1 regulates systemicacquired resistance through both NONEXPRESSOR OF PR1 (NPR1) gene-dependent and SA accumulation-dependent pathways (45).…”
Section: Discussionmentioning
confidence: 99%
“…©2011 KSMCB 1 mental responses, including heat shock, pathogen defense, drought and cold tolerance, ABA signaling, flowering, and phosphate deficiency (Catala et al, 2007;Jin et al, 2008;Lee et al, 2007;Miura et al, 2005;2009;Saracco et al, 2007;Yoo et al, 2006). Recently, van den Burg et al (2010) reported that AtSUMO3 acted downstream of SA accumulation, while involvement of AtSUMO1 and AtSUMO2 has been reported in suppressing SA accumulation.…”
Section: Molecules and Cellsmentioning
confidence: 99%
“…Anthocyanin levels were determined in 2-wk-old plants according to Catala and colleagues (41). ROS accumulation was visualized and quantified in 2-wk-old plants with NBT and DCFH 2 -DA, respectively, as described (42).…”
Section: Methodsmentioning
confidence: 99%